Barrier membranes for periodontal guided bone regeneration: a potential therapeutic strategy - Wang, Dongxue; Zhou, Xuchang; Cao, Hong; Zhang, Huawei; Wang, Daping; Guo, Jianming; Wang, Jifeng (Frontiers in Materials, 2023)
Periodontal disease is one of the most common oral diseases with the highest incidence worldwide. In particular, the treatment of periodontal bone defects caused by periodontitis has attracted extensive attention. Guided bone regeneration (GBR) has been recognized as advanced treatment techniques for periodontal bone defects. GBR technique relies on the application of barrier membranes to protect the bone defects. The commonly used GBR membranes are resorbable and non-resorbable. Resorbable GBR membranes are divided into natural polymer resorbable membranes and synthetic polymer resorbable membranes. Each has its advantages and disadvantages. The current research focuses on exploring and improving its preparation and application. This review summarizes the recent literatures on the application of GBR membranes to promote the regeneration of periodontal bone defects, elaborates on GBR development strategies, specific applications, and the progress of inducing periodontal bone regeneration to provide a theoretical basis and ideas for the future application of GBR membranes to promote the repair of periodontal bone defects.